(untitled) (Global Journal of Medical Research, 2023)
Introduction Tranexamic acid TXA is indicated for the control and prevention of hyperfibrinolysis-induced hemorrhages because it promotes increased clot stability 11 Since its pre-hospital use is not yet well-defined the purpose of this article is to evaluate the scientific research on its mechanism of action indications and contraindications to supplement the risk-benefit discussion Methodology The current study is a literature review the database of which was taken from the SciELO Scientific Electronic Library Online and PubMed platforms